2020
DOI: 10.21203/rs.3.rs-125343/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age and Multimorbidities as Poor Prognostic Factors for COVID-19 in Hemodialysis: a Lebanese National Study

Abstract: BackgroundHemodialysis patients with COVID-19 have been reported to be at higher risk for death than the general population. Several prognostic factors have been identified in the studies from Asian, European or American countries. This is the first national Lebanese study assessing the factors associated with SARS-CoV-2 mortality in hemodialysis patients.MethodsThis is a cross-sectional study that included all chronic hemodialysis patients in Lebanon who were tested positive for SARS-CoV-2 from 31st March to … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
1
2
0
3
Order By: Relevance
“…The selection process is illustrated in Figure 1. The 22 included studies 1637 were from 17 countries, with a total of 13,191 patients. Meta-analysis of epidemiological, clinical, and radiological data from COVID-19 patients undergoing MHD are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection process is illustrated in Figure 1. The 22 included studies 1637 were from 17 countries, with a total of 13,191 patients. Meta-analysis of epidemiological, clinical, and radiological data from COVID-19 patients undergoing MHD are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies 1617,2123,25,2733,35 reported data regarding treatment(s). Almost all patients underwent symptomatic treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Trata-se de um segmento da população com elevada vulnerabilidade, 4 não passível de confinamento restrito, devido à necessidade de receber tratamento regular pelo menos três vezes por semana. Existe, por isso, a necessidade de deslocação em transporte maioritariamente partilhado o que, apesar do esforço realizado pelas autoridades de saúde e por todos os operadores envolvidos em garantir as condições de segurança ideais, representa um risco acrescido.…”
Section: Introductionunclassified
“…■ Alrededor del 40% de los pacientes pasaron por una enfermedad leve controlada desde su domicilio, según dos artículos revisados Por lo tanto, la presentación grave de la enfermedad se presentó al menos en la mitad de la población de estudio. La principal causa de hospitalización y enfermedad grave fue la hipoxia 17 . Además, se relacionó la hospitalización con pacientes de mayor edad, fumadores, con arritmias o con dependencia 25 .…”
Section: Se Analizaron 8 Artículos Para Determinar El Curso Clínico D...unclassified
“…■ Edad avanzada. La edad mayor a 65 años es un potente predictor de mortalidad 17,23 , aunque la mayor tasa de fallecimientos por COVID-19 en la población en diálisis se registra en el grupo de edad de entre 75-80 años 22,25 .…”
Section: Los Factores De Riesgo De Mortalidad Más Mencionados En Los ...unclassified